2021
DOI: 10.1371/journal.pone.0249252
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood groups with presentation and outcomes of confirmed SARS CoV-2 infection: A prospective study in the largest COVID-19 dedicated hospital in Bangladesh

Abstract: Background Globally, studies have shown conflicting results regarding the association of blood groups with SARS CoV-2 infection. Objective To observe the association between ABO blood groups and the presentation and outcomes of confirmed COVID-19 cases. Design, setting, and participants This was a prospective cohort study of patients with mild-to-moderately severe COVID-19 infections who presented in the COVID-19 unit of Dhaka Medical College Hospital and were enrolled between 01 June and 25 August, 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Blood group A was prevalent in their population (42.8%) and it was statistically associated with increased infection risk of COVID-19 (OR: 1.33, 95% CI: 1.02-1.73, p=0.04) in their female population [11]. Two recent studies from the subcontinent: one from Peshawar, Pakistan, and the other from Dhaka, Bangladesh have demonstrated the susceptibility of COVID-19 with the ABO blood groups [12,13]. The study from Pakistan had a sample size of 1935 patients, with blood group B as the prevalent blood type (35.9%) with an increased susceptibility for COVID-19 infection (OR: 1.195 (95% CI: 1.04-1.36), p=0.009) while blood groups A and O did not have statistically significant association of positive RT-PCR for SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Blood group A was prevalent in their population (42.8%) and it was statistically associated with increased infection risk of COVID-19 (OR: 1.33, 95% CI: 1.02-1.73, p=0.04) in their female population [11]. Two recent studies from the subcontinent: one from Peshawar, Pakistan, and the other from Dhaka, Bangladesh have demonstrated the susceptibility of COVID-19 with the ABO blood groups [12,13]. The study from Pakistan had a sample size of 1935 patients, with blood group B as the prevalent blood type (35.9%) with an increased susceptibility for COVID-19 infection (OR: 1.195 (95% CI: 1.04-1.36), p=0.009) while blood groups A and O did not have statistically significant association of positive RT-PCR for SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%
“…A single-centre study from Bangladesh which evaluated 438 patients with SARS-CoV-2 infection also found a significantly higher rate of blood group A amongst COVID-19 patients compared to the general population [20]. However, ABO blood groups were not associated with type of presentation or recovery from infection [20]. Conversely, an observational study of 14,112 individuals tested for SARS-CoV-2 in the New York Presbyterian hospital system found that risk of intubation was increased for AB and B blood groups but decreased for A when compared to O blood group and risk of death was increased for those with AB blood group and decreased for A and B blood groups [19].…”
Section: Abo Blood Group Covid-19 and Cvdmentioning
confidence: 94%
“…A single-centre study from Bangladesh which evaluated 438 patients with SARS-CoV-2 infection also found a significantly higher rate of blood group A amongst COVID-19 patients compared to the general population [20]. However, ABO blood groups were not associated with type of presentation or recovery from infection [20].…”
Section: Abo Blood Group Covid-19 and Cvdmentioning
confidence: 99%
See 2 more Smart Citations